Proposta para tomada de decisão na aquisição de robôs de soldagem em indústrias de pequeno porte pelo método TCO - Souza, Vinícius Pereira de (2023)
Industrial scenarios develop at an accelerated pace, since the parameters for series production are systematically changing, in a trend of frank technological expansion guided by Industry 4.0. Developing new production systems, maintaining acceptable process parameters, contributes to the vanguard of modern manufacturing organizations. Producing with quality, on a large scale and at low cost is what motivates us every day, in the face of an economic scenario of constant challenges and changes. The modernization of machines and equipment adds to this, making everyday life in the industry efficient, as it directly involves changing robust manufacturing processes to essentially technological processes that are easy to control and quick to respond. Therefore, this work aims to develop a proposal for decision-making in the acquisition of welding robots in small industries using the TCO method. This methodological proposal was designed to elucidate managerial actions in companies, in this business context, indicating the best option at critical moments, where resources must be channeled correctly, with little room for mistakes and with satisfactory results in a short period of time. time. The TCO economic analysis method was used as a reference, parameterized by factors observed as essential in this evaluation model. The main results were the validation of the differentiation between initial purchase costs and costs throughout the life cycle of the equipment, since these, when mapped correctly and considered in the final purchase evaluation, make decision-making more assertive.